DEVELOPMENT OF AGRICULTURE SECTOR IN POVERTY REDUCTION IN EAST JAVA (Study of GKS Plus-GERBANGKERTASUSILA Plus Period 2010-2017) - Wandi Abbas; Abid Muhtarom (International Journal of Economics Management and Social Science, 2018)
Gerbangkertasusila Plus (GKS Plus). The Government sees the need for a new support area of GKS PLUS to increase the carrying capacity of the core city. The purpose of this research is to realize the idea of Spatial Information System in East Java. The method used in this research is the regression model that will be estimated. The data used in this research is panel data of 2010-2017 period based on GKS Plus area of Surabaya City to regency / city of Gresik, Bangkalan, Mojokerto, Sidoarjo, Lamongan, Bojonegoro, Tuban, Jombang and Pasuruan. The results showed that the area of land, labor and irrigation have a positive impact on poverty. It shows that the agricultural sector provides very small value added, thus affecting the increase of poverty in Gerbangkertasusila Plus (GKS Plus).